Ahl al-Hadith Methodologies on Qur’anic Discourses in the Ninth Century: A Comparative Analysis of Ibn Hanbal and al-Bukhari - Azmi, Ahmad Sanusi (Online Journal of Research in Islamic Studies, 2017)
The depth focus of mufassirun on linguistic sciences creates the pattern and nature of Qur’anic discourse in the ninth century. However, it was not only mufassirun who appeared to direct their focus on lexical explanation in their tafsir, the massive production of Qur’anic works that concentrate on literary analysis indicates clearly the nature and tenor of Qur’anic discourse within this period. This includes the works of ahl al-hadith of the early century. This study aims to (1) explore ahl al-hadith methodology in Qur’anic discourse, particularly of Ahmad ibn Hanbal and al-Bukhari,(2) extract their idiosyncratic approaches and (3) elucidate their personal style on certain issues regarding the Qur’an. The study is qualitative in nature in which the researcher employed both critical and analytical methods. The study in its finding asserts that Ahmad and al-Bukhari provide a different explanation of the Qur’anic verses from that of the mufassirun and sira’s authors. For instance, in the interpretation of 94:1, Ahmad ibn Hanbal and al-Bukhari clearly demonstrates his arrival at a different interpretation and perspective.